Alternative entry receptors for herpes simplex virus and their roles in infection and disease. (September 2007) - Spear, Patricia G; Manoj, Sharmila; Yoon, Miri; Taylor, Joann M; Lin, Erick; Susmarski, Nanette
Herpes simplex virus (HSV) infections are highly prevalent in human populations. Clinical manifestations are often not apparent or are limited to mucocutaneous lesions, at least in persons other than neonates or the immunocompromised. The virus establishes latent infections in peripheral neurons, cannot be eliminated by the immune system once acquired and can periodically reactivate to cause recurrent skin lesions even in persons with apparently normal immune systems. Additionally, the virus can spread to the CNS, causing life-threatening encephalitis. Multiple alternative entry receptors for HSV have been identified. This review will focus on recent studies designed to investigate which of these receptors are exploited by the virus for infection of its various target cell types, whether each receptor contributes equally to disease, and whether HSV strains differ in receptor usage, perhaps influencing their pathogenicity.